A Study on Internship Student Debriefing Materials in ‘Merdeka Belajar Kampus Merdeka’ Program - Handrianto, Budi (Diversity: Jurnal Ilmiah Pascasarjana, 2021)
The VUCAS era as it is today has brought about changes in attitudes and human interactions at work. A person’s competancy is demanded to be acquired more than one or what is so called, multitasking. Whilst, higher education Institutions does not prepare these competencies for graduate students. The industrial world is also overwhelmed by the quality of untrained new employees. There for, it is esential to create program in order to link and match between Higher Education Institutions Programs and the need of industrial world. The Ministry of Education and Culture has created a 3 semesters training program outside its study program, one of which is an internship in companies. Due to this, we design debriefing material in accordance to the industrial perspective. This research aims to obtain perspectives on the material from the industry. This qualitative research was conducted using in-depth interviews, both in person and online to gather information from industry players. The results obtained will be materials that must be given to students during the debriefing, there are two important materials to be given, namely; knowledge and work attitude. Knowledge includes: company organization, job duties and responsibilities, remuneration systems, industrial relations, employee development and management systems. Work attitudes include general values such as integrity, discipline, leadership, team work, interpersonal skills, analitical competency, open mindedness, emotional quotient (EQ), burning desire/passion and time management skills and rules in work (manner).